Diglosia en jóvenes hablantes de la lengua Shuar en la comunidad de Pupunas, cantón Limón Indanza, Morona Santiago - Vega Sharup, Tony Savio (2025)
This study examines diglossia as a phenomenon currently occurring among young speakers of ancestral Shuar language in Pupunas Indigenous Community, located in Limón Indanza Canton, Morona Santiago Province - Ecuador. The research addresses the growing movement of Shuar youth towards the use of Spanish, a language perceived as more prestigious, over their ancestral language. The adoption of Spanish has contributed to the gradual erosion of Shuar, which has been preserved by people in the Pupunas community through generations. This study adopted a mixed-method, non-experimental research design. Data were gathered through interviews and surveys, using an interview protocol and a questionnaire as primary data collection instruments. Participants were selected through purposive, non-probabilistic sampling. The findings indicate that young Shuar speakers predominantly use Spanish in daily communication. The routinary use of Spanish clearly reflects a shift in their language preference. This shift not only highlights the dominance of Spanish in educational and social spheres but also reveals the progressive weakening of the Shuar language. The diglossia situation fosters linguistic displacement, as Spanish offers greater opportunities for academic, professional, and social advancement. This study suggests that diglossia has led to a decline in the intergenerational transmission of the Shuar language, resulting in cultural and linguistic disparity within the community. This process represents a serious threat to the survival of Shuar as an ancestral language that has survived across generations despite adverse conditions.